2006
DOI: 10.1534/genetics.106.062117
|View full text |Cite
|
Sign up to set email alerts
|

Ltv1 Is Required for Efficient Nuclear Export of the Ribosomal Small Subunit in Saccharomyces cerevisiae

Abstract: In eukaryotes, 40S and 60S ribosomal subunits are assembled in the nucleus and exported to the cytoplasm independently of one another. Nuclear export of the 60S requires the adapter protein Nmd3, but no analogous adapter has been identified for the 40S. Ltv1 is a nonessential, nonribosomal protein that is required for 40S subunit biogenesis in yeast. Cells lacking LTV1 grow slowly, are hypersensitive to inhibitors of protein synthesis, and produce about half as many 40S subunits as do wild-type cells. Ltv1 int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
106
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(115 citation statements)
references
References 55 publications
(87 reference statements)
8
106
1
Order By: Relevance
“…Of these, human Rio2 has been shown to have a sequence in its C terminus, deletion of which significantly reduces the rate of pre-40S export in human cells (Zemp et al 2009). In yeast, both Dim2 and Ltv1 have been proposed as pre-40S adapters (Seiser et al 2006;Vanrobays et al 2008). However, the proposed NES in Dim2 does not match the new structure-based LR-NES consensus (Guttler et al 2010), and a possible NES in Ltv1 (aa 169-176) was later shown by us to be important for cytoplasmic maturation, but not export (Fassio et al 2010).…”
mentioning
confidence: 97%
“…Of these, human Rio2 has been shown to have a sequence in its C terminus, deletion of which significantly reduces the rate of pre-40S export in human cells (Zemp et al 2009). In yeast, both Dim2 and Ltv1 have been proposed as pre-40S adapters (Seiser et al 2006;Vanrobays et al 2008). However, the proposed NES in Dim2 does not match the new structure-based LR-NES consensus (Guttler et al 2010), and a possible NES in Ltv1 (aa 169-176) was later shown by us to be important for cytoplasmic maturation, but not export (Fassio et al 2010).…”
mentioning
confidence: 97%
“…The factors involved in 40 S export are largely unknown, but the non-essential pre-40 S factor Ltv1 was suggested to play a role in this process (6). Following nuclear export, the pre-40 S subunit undergoes cytoplasmic maturation, involving two major events.…”
mentioning
confidence: 99%
“…These proteins are involved in a variety of cellular pro- cesses such as membrane cytoskeleton assembly (Sla2 [32]), mitotic spindle assembly (Spc72 [35]), and chromatin modification (Hpa3 [77]). For Ltv1, a role in the Xpo1-mediated export of small ribosomal subunits has recently been shown (59). No function has been assigned to Sgm1 so far, and with the exception of Ltv1, none of the proteins found in our screen has been analyzed with respect to a possible function in nuclear export.…”
Section: Resultsmentioning
confidence: 92%